2021
DOI: 10.1097/cm9.0000000000001824
|View full text |Cite
|
Sign up to set email alerts
|

Switching from efavirenz to elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide reduces central nervous system symptoms in people living with HIV

Abstract: Background: Central nervous system (CNS) symptoms after efavirenz (EFV) treatment in people living with human immunodeficiency virus (HIV) could persist and impact their quality of life. We assessed the impact of EFV-based regimen replacement with elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF), which is considered an alternative option for subjects who do not tolerate EFV. Most specifically, we assessed the safety and the efficacy of E/C/F/TAF and its effects on the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
3
0
0
Order By: Relevance
“…Our study showed that after excluding the economic burden between ARTs, BIC/FTC/TAF had significant better persistence compared with EFV + 3TC + TDF, which is consistent with previous real-world studies in western countries [ 10 , 11 ]. The treatment discontinuation of EFV + 3TC + TDF group is mainly due to safety reason, which is also shown in other studies reporting the neuropsychiatric side effects related with EFV [ 14 16 ]. Our study result is consistent with previous study findings showing EFV-based regimen to increase the treatment discontinuation risk due to neuropsychiatric side effects [ 17 19 ].…”
Section: Discussionsupporting
confidence: 64%
“…Our study showed that after excluding the economic burden between ARTs, BIC/FTC/TAF had significant better persistence compared with EFV + 3TC + TDF, which is consistent with previous real-world studies in western countries [ 10 , 11 ]. The treatment discontinuation of EFV + 3TC + TDF group is mainly due to safety reason, which is also shown in other studies reporting the neuropsychiatric side effects related with EFV [ 14 16 ]. Our study result is consistent with previous study findings showing EFV-based regimen to increase the treatment discontinuation risk due to neuropsychiatric side effects [ 17 19 ].…”
Section: Discussionsupporting
confidence: 64%
“…After 48 weeks’ follow-up, no viral drug resistance or improvement in neuropsychiatric symptoms was found in patients switching from NNRTIs to E/C/F/TAF [6] . In our previous study, neuropsychiatric symptoms improved after switching from efavirenz [7] . In the present study, switching to E/C/F/TAF was associated with a lower proportion of hepatic insufficiency and increased triglyceride levels.…”
supporting
confidence: 57%
“…[6] In our previous study, neuropsychiatric symptoms improved after switching from efavirenz. [7] In the present study, switching to E/C/F/TAF was associated with a lower proportion of hepatic insufficiency and increased triglyceride levels. E/C/F/TAF therapy thereby appeared safe and may alleviate toxicity, while also leading to improvements in symptoms.…”
supporting
confidence: 49%